Instrumental and noninstrumental procedural justice: differential effects on organizational citizenship behavior / Aizzat Mohd. Nasurdin and T. Ramayah (Faculty of Business and Management ; UiTM Press, 2005)
The purpose of this paper is to examine the differential effects of the instrumental and noninstrumental components of procedural justice on the two components of organizational citizenship behavior (OCBO and OCBI). Based on the social exchange framework (Blau, 1964), the norm of reciprocity (Gouldner, 1960), and the "group-value" model (Lind & Tyler, 1988), a study was conducted among Malaysian employees working in the hotel industry. Regression analyses on a sample of 188 employees showed that instrumental procedural fairness had a positive and significant effect on OCBI instead of OCBO. On the other hand, noninstrumental procedural justice had a positive and significant impact on OCBO instead of OCBI. Hence, both hypotheses were not supported. Findings and implications for managerial practice are discussed.